Pentapartitioned Neutrosophic Probability Distributions - Suman Das; Bimal Shil; Rakhal Das; Huda E. Khalid; A. A. Salama (Neutrosophic Sets and Systems, 2022)
In this manuscript, we introduce and study some pentapartitioned neutrosophic probability distributions. The study is done through the generalization of some classical probability distributions as Poisson distribution, Exponential distribution, Uniform distribution etc. This study opens the way for dealing with issues that follow the classical distributions and at the same time contains data not specified accurately.